2022
DOI: 10.1136/bjophthalmol-2021-319807
|View full text |Cite
|
Sign up to set email alerts
|

Retinal age gap as a predictive biomarker for mortality risk

Abstract: AimTo develop a deep learning (DL) model that predicts age from fundus images (retinal age) and to investigate the association between retinal age gap (retinal age predicted by DL model minus chronological age) and mortality risk.MethodsA total of 80 169 fundus images taken from 46 969 participants in the UK Biobank with reasonable quality were included in this study. Of these, 19 200 fundus images from 11 052 participants without prior medical history at the baseline examination were used to train and validat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 37 publications
2
59
0
Order By: Relevance
“…Our results are in line with other reports which have demonstrated that DL algorithms can use retinal images to predict modifiable CVD risk factors, including diabetes, hypertension, and cholesterol [25,27,29,[46][47][48] and non-modifiable risk factors such as chronological age and gender [24]. However, like the Framingham equations, the algorithms published to date are unable to examine the relative contribution of each of the individual factors that comprise risk as they utilize a statistical method which imposes linearity between the individual parameters used during analysis.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in line with other reports which have demonstrated that DL algorithms can use retinal images to predict modifiable CVD risk factors, including diabetes, hypertension, and cholesterol [25,27,29,[46][47][48] and non-modifiable risk factors such as chronological age and gender [24]. However, like the Framingham equations, the algorithms published to date are unable to examine the relative contribution of each of the individual factors that comprise risk as they utilize a statistical method which imposes linearity between the individual parameters used during analysis.…”
Section: Discussionsupporting
confidence: 93%
“…To define a model of healthy cardiovascular ageing, as previously validated in other organ systems, 11,5961 we first partitioned the 39,559 participants into a development set, which consisted of 5065 “healthy” individuals that were free of cardiac, metabolic or respiratory disease, with a body mass index below 30 (see Supplementary Material for details). We randomly split this group into separate training (80%, n = 4021) and test (20%, n = 1044) sets.…”
Section: Methodsmentioning
confidence: 99%
“…Incident CVD events were defined as the first occurrence of CVD events during the follow-up period, from the baseline examination to The development and validation of the DL model for age prediction were described in details elsewhere. 22 Briefly, all fundus images were preprocessed and fed into a DL model using a Xception architecture. Data augmentation was performed during training using random horizontal or vertical flips.…”
Section: Cvd Ascertainmentmentioning
confidence: 99%